(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article concerns the issues of intercultural and inter-civilizational relations that have been between the ancient Turkis and European countries in many centuries. The main goal set by the authors of the article is to summarize and, as soon as possible, systematize the achievements of the Turkic peoples, to objectively present the role of the Turks in world civilization, to debunk the Eurocentrist myths and stereotypes that are still dominant in science, belittling, distorting or belittling the role of the Turks in the history of mankind. Turkic world throughout history is a unique place – the birthplace of the first and most powerful of cultures and civilizations, it later turned out decisive influence on the entire course of world history. Thus, a feature of Turkic culture is that it is inevitably absorbed all the best from the world of East and West cultures, but incorporating these values, it has managed to preserve and its unique and distinctive culture. The authors draw attention to these historical sources testifying to the existence in ancient times of diplomatic relations between the rulers and the khans of the Great Steppe of Dasht-i-Kipchak, with different other states, countries and nations as in the West, and in the East as well. There Turkic a decisive impact on the emergence and development of the culture of European countries of the Middle Ages. Key words: Ancient Turkic Culture, Great Silk Road, Great steppe, diplomacy, hunnu, turks.